Business valuation : an integrated theory - Mercer, Z. Christopher; Harms, Travis W. (John Wiley & Sons, Inc., 2021)
"More than a decade after the publication of Business Valuation: An Integrated Approach, second edition, the core concepts of the integrated theory remain the same. Business value, at any level, is a function of expected cash flows, expected risk, and the expected growth of the cash flows. The second edition was written from the perspective of valuing the net equity of companies. As a result, the emphasis was on equity cash flows and equity discount rates. This analysis remains valid and will be extended. However, during this time, there has been an increasing awareness among appraisers that private companies are bought and sold on an enterprise value basis, inclusive of equity and debt, and not with reference to net equity value alone. The third edition will extend the analysis and concepts to an enterprise value basis. The basic theory of the second edition will be extended to incorporate enterprise cash flows (to equity and debt), enterprise discount rates and the weighted average cost of capital, and enterprise growth rates. This new edition will feature increased emphasis on the discounted cash flow method in the development of enterprise level values for businesses"- Resumé vydavatel
Includes index.
Keywords: podniky; obchodní společnosti; oceňování podniků; cash flow; business enterprises; corporations; valuation of business enterprises; elektronické knihy; kolektivní monografie; electronic books; collective monographs